Viral Transgene Expression Delivered by Repeat Intraocular Adenoviral Vector Injection: in Vivo Live Imaging Study - Peter L. Gehlbach; Roy S. Chuck; Chung-Gyu Park; Choul Yong Park (Molecular Imaging)
We delivered adenovirus vector (Ad) via intravitreous injection and monitored transgene (luciferase) expression in living mice (BALB/c) at multiple time points. In vivo live imaging technology was able to assess dynamically intraocular luciferase expression in a single animal population throughout the entire experiment period. Using this information, we were able to determine the optimal time point for readministration of Ad into the eyes and to dynamically study the time course of expression of a second Ad administration. Optical imaging demonstrated the limited period of transgene expression in eyes. Significant transgene signal was also detected in livers. The repeat intraocular delivery of the adenovirus resulted in significant blunting of transgene expression in both eyes and livers compared to the initial delivery. Periocular corticosteroid (triamcinolone acetonide) injection combined with initial Ad delivery was effective to rescue luciferase expression on repeat Ad vector delivery. However, this effect was not observed when corticosteroid was combined with repeat Ad delivery. Although corticosteroid enhanced ocular transgene expression, it also increased transgene expression in liver, which has potential safety implications. This dynamic transgene expression in eyes was successfully traced and monitored via a live imaging technique.